Pemanfaatan Sistem Absensi Berbasis RFID Sebagai Upaya Meningkatkan Akurasi dan Efisiensi Kehadiran Perangkat Desa di Aikmel Barat - Sudianto, Aris; Muhammad Djamaluddin; Lalu Kertawijaya; Jumawal; Ida Wahidah (Universitas Hamzanwadi, 2025)
The attendance of village officials is an important factor in supporting the quality of administrative services and governance at the village level. However, the manual attendance process previously used at the Aikmel Barat Village Office often resulted in several issues, such as delays in recording, inaccurate data, and low administrative efficiency. This community service activity aims to implement a Radio Frequency Identification (RFID)-based attendance system as a solution to improve the accuracy and efficiency of recording village officials’ attendance. The implementation methods included system needs assessment, installation of RFID devices, development of supporting applications, training for village officials, and evaluation of system performance after implementation. The results show that the RFID-based attendance system is capable of recording attendance automatically, quickly, and more accurately compared to the manual method. In addition, the use of RFID technology helps improve work discipline through more precise time logging and simplifies the process of recapitulating attendance data. User evaluations also indicate a high level of satisfaction, as the system is considered easy to use and enhances work efficiency. This implementation is expected to serve as a model for technology adoption to support the digitalization of village administration and improve the quality of public services in Aikmel Barat.